A fairness‐aware distributed dual‐hop heterogeneous half and full‐duplex link scheduling for 6G network. Issue 6 (26th April 2021) - Guan, Zheng; Hu, Yang; Yang, Zhijun; He, Min; Marco, Anisetti
Abstract: Current network technologies evolve toward the sixth generation of mobile communications (6G) systems. To achieve the performance requirements of high data rate, low latency, and massive connection, full‐duplex (FD) wireless communication is one possible solution to provide high throughput and channel utilization. However, it is difficult to do so for legacy communication nodes. A distributed fairness‐aware full‐duplex dual‐hop link scheduling algorithm, named weighted full duplex (W‐FD), is proposed to achieve the efficient node selection and dynamic relay probing. The scheduling weight that considered traffic load, mutual interference, and response interval is employed to ensure link load balance. A node with a higher scheduling weight in the neighborhood is selected as the link establishment object to build a full‐duplex link. Better than conventional half‐duplex(HD) link scheduling, W‐FD reduces link scheduling interval and ensures the access opportunities for legacy nodes. Simulation result shows that throughput and delay performance are improved. Compared with the existed full‐duplex link scheduling, W‐FD could better reflect the fairness of scheduling in multi‐nodes and asymmetric‐packets networks, and ensure the throughput and delay performance. Abstract : A distributed fairness‐aware full‐duplex dual‐hop link scheduling algorithm (W‐FD) is proposed to achieve the efficient node selection and dynamic relay probing scheme for 6G network. It reduces link scheduling intervals and ensures the access opportunities for legacy nodes.